Effect of Education and Earning Level on Social Capital of Amol City's Veterans: A Sociological Analysis - H. Janalizadeh Choob Basti; F. Moradi (Afarand Scholarly Publishing Institute, 2014)
Aims: The Iran-Iraq war is a momentous event in Iranian peoples' life. Various social stratum including veterans have played an effective role to defense Iran Islamic revolution and the country. This study aimed to investigate the role of education and income level on social capital of veterans. Materials & Methods: This cross-sectional study was done on 522 veterans with document and exact percent of devotee recorded at Foundation of Martyrs and Veterans Affairs of the Amol City in 2011. Subjects were selected by simple random sampling. Data were collected using researcher-made questionnaire containing 24 questions. Data were analyzed using SPSS 16 and One-way ANOVA test. Findings: The mean number of reliable neighbors of veterans was 4.62±9.17 persons, the mean number of reliable friends was 6.43±1.29 persons and the mean number of reliable relatives was 16.35±3.16 persons. The subjects had less trust to the society overall and they were stated that they were respected less by the society compared to their family and the Martyrs Foundation. Educational level just had significant effect on veterans' utilization of friends and income level just had significant effect on having reliable neighbors. The effect of educational level solely had significant effect on social capital of respect and trust to the society and income rate on veterans' utilization of mental social capital was significant in all three areas.    Conclusion: Going from inter-group level (family and relatives) towards extra-group level (the Martyrs and Veterans Foundation and the society), veterans' utilization of both two social capital types decreases.